Table of Content - - (Journal of Economic, Administrative and Legal Sciences, 2023)
Table of Content:1. The relationship between educational capabilities and entrepreneurial performance A study on a sample of service sector establishments operating in the state of Khartoum, 2022Dr. Hassan Abdul Rahim Fadl Muhammad, Dr. Sheikh Muhammad al-Khidr Muhammad, Dr. Hudhayfah bin Hadi Madkhali, Dr. Anis Muhammad Salih Souissi2. The role of creative leadership in achieving institutional excellenceMr. Ahmed Hassan Alshekhi, D. Osama Abdul Rahman Mujallid3. Unified legal regulation of bank interest and commissions - A comparative study between Islamic law and law –Mr. Haitham Ismail Muhammad Al-Baydani4. Arbitration in public project disputes in the Law of Saudi ArabiaDr. Hashem Baker Alshaikh5. The reality of the role of the Presidency of the Grand Mosque and the Prophet's Mosque  in managing the crisis under the COVID-19 pandemic is a modelMr. Tariq Khames Al-Zahrani6. The Impact of the Work Environment on the Performance of Nurses in the Saudi Healthcare SectorKhaled Mansour Al-Thabeti, Amani Hassan Al-Dharawi, Haya Ali Al-Mabrouk, Abrar Fawaz Al-Fayez, Obaid Ali Al-Khairy, Ali Hassan Al-Rashdi, Belkhair Muhammad Abdullah, Badra Ibrahim Al-Zubaidi, Abdullah Ali Al-Khairy, Fares Suleiman Al-Jaloud7. Technical Services for Organizing Crowds, Provided to Pilgrims, During Hajj SeasonDr. Abdulaziz Mohammed Choudhry, Mr. Mansour Attia Al-Maliki, Mr. Wissam Walid Khurshid, Mr. Yasser Taj Shawli8. Forensic accounting and the current state of the infrastructure components of its implementationDr. Osama Issam Matar
Keywords: Journal of Economic, Administrative and Legal Sciences